Insurance Aspects of Incoterms and the Cargo Insurance - Andreeva, Tsvetelina (Research Papers, 2019)
The service of the international trade is expressed in the conclusion of a trade contract, insurance, transport and other important activities.The study explores the essence and specific features of the international trading terms Incoterms and the Institute Cargo Clauses, which are interrelated. Incoterms are mainly investigated with regard to their insurance aspects, which are a prerequisite for the conclusion of cargo insurance.The world-wide well recognized and applied Institutional Cargo Clauses are examined as specific and specialized cargo insurance terms. Besides from the point of view of who is responsible for transportation (transport costs), insurance (insurance costs) and others, the study focuses on their specificity and diversity.The aim of the study is to highlight the need, the essence and expand the popularity of cargo insurance by achieving real, complete and effective cargo insurance. To accomplish this goal, it is the task to reveal the practical nature and specificity of commercial contracts and insurance conditions. The research was carried out by methods of functional analysis and summary.As a result of the study, specific findings, conclusions and recommendations with practical purpose are identified.In this way, the subject matter will provide for more massive and more efficient cargo insurance, will stimulate the development of the international trade (export, import and re-export), trade in national borders, will facilitate its study by the practitioners and scientists.The research is useful both for foreign trade and insurance branches, as well as for students.
Keywords: Incoterms; Cargo; Institute cargo clauses; Terms; Insurance cover and exclusions